Cybersecurity, Bureaucratic Vitalism and European Emergency. (March 2015) - Simon, Stephanie; de Goede, Marieke
Securing the internet has arguably become paradigmatic for modern security practice, not only because modern life is considered to be impossible or valueless if disconnected, but also because emergent cyber-relations and their complex interconnections are refashioning traditional security logics. This paper analyses European modes of governing geared toward securing vital, emergent cyber-systems in the face of the interconnected emergency. It develops the concept of 'bureaucratic vitalism' to get at the tension between the hierarchical organization and reductive knowledge frames of security apparatuses on the one hand, and the increasing desire for building 'resilient', dispersed, and flexible security assemblages on the other. The bureaucratic/vital juxtaposition seeks to capture the way in which cybersecurity governance takes emergent, complex systems as object and model without fully replicating this ideal in practice. Thus, we are concerned with the question of what happens when security apparatuses appropriate and translate vitalist concepts into practice. Our case renders visible the banal bureaucratic manoeuvres that seek to operate upon security emergencies by fostering connectivities, producing agencies, and staging exercises.